The Influence of Repurchase on Fresh Food (Case Study of Sayurbox) - Masfufatun Nur; Arief Bowo Prayoga Kasmo (Dinasti International Journal of Management Science, 2023)
The growing online grocery stores have become an attractive choice for consumers to shop for their daily fresh ingredients. This research analyzes the impact of perceived price, product quality, perceived value, and satisfaction on the repurchase intention of fresh food in Sayurbox. The results of the proposed hypothesis were tested using structural equation model on 180 respondents to show that perceived value and product quality contributed to influencing consumer perceived value. Perceived value has been found to be highly correlated with satisfaction, and increased value received by consumers increases satisfaction. Research also reveals that satisfaction has a significant impact on repeat purchase intention. Higher satisfaction means consumers are more likely to shop at the same place. Furthermore, the moderation delivery between perceived value and satisfaction has a positive effect but significant effect, suggesting that delivery influences customer response.